Electro-Sorption of Hydrogen by Platinum, Palladium and Bimetallic Pt-Pd Nanoelectrode Arrays Synthesized by Pulsed Laser Ablation - Antonino Scandurra; Maria Censabella; Antonino Gulino; Maria Grazia Grimaldi; Francesco Ruffino (Micromachines, 2022)
Sustainable and renewable production of hydrogen by water electrolysers is expected to be one of the most promising methods to satisfy the ever-growing demand for renewable energy production and storage. Hydrogen evolution reaction in alkaline electrolyte is still challenging due to its slow kinetic properties. This study proposes new nanoelectrode arrays for high Faradaic efficiency of the electro-sorption reaction of hydrogen in an alkaline electrolyte. A comparative study of the nanoelectrode arrays, consisting of platinum or palladium or bimetallic nanoparticles (NPs) Pt80Pd20 (wt.%), obtained by nanosecond pulsed laser ablation in aqueous environment, casted onto graphene paper, is proposed. The effects of thin films of perfluoro-sulfonic ionomer on the material morphology, nanoparticles dispersion, and electrochemical performance have been investigated. The NPs-GP systems have been characterized by field emission scanning electron microscopy, Rutherford backscattering spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, cyclic voltammetry, and galvanostatic charge-discharge cycles. Faradaic efficiency up to 86.6% and hydrogen storage capacity up to 6 wt.% have been obtained by the Pt-ionomer and Pd/Pt80Pd20 systems, respectively.